Современные подходы в ДНК-диагностике наследственных болезней - Калинин, В.Н. (Биополимеры и клетка, 1990)
На основании литературных и собственных данных рассматриваются четыре основных подхода, используемых в настоящее время для диагностики наследственных болезней человека на уровне ДНК. Различные подходы применяются в зависимости от того, известен ли ген, с которым связано заболевание, мутации в нем и характер мутаций. Дальнейшее совершенствование методов ДНК-диагностики и расширение их практического использования будет связано с развитием и разработкой новых методов генетической инженерии, в частности, с выборочной амплификацией определенных участков генома при помощи полимеразной цепной реакции. З огляду на літературні і власні дані розглянуто чотири основних підходи, використовувані на даний час для діагностики спадкових хвороб людини на рівні ДНК. Різні підходи застосовують залежно від того, чи відомий ген, з яким пов'язано захворювання, мутації в ньому і характер мутацій. Подальше вдосконалення методів ДНК-діагностики та розширення їхнього практичного використання будуть пов'язані з розвитком і створенням нових підходів генетичної інженерії, зокрема, з вибірковою ампліфікацією певних ділянок геному за допомогою полімеразної ланцюгової реакції. Advantage in principle of DNA-diagnosis is that it is performed at the level of the original cause of a hereditary disease, by detection of the damaged gene and identification of the nature of its structural anomaly. DNA-diagnosis is especially effective in prenatal and preclinical diagnosis, in heterozygote carrier detection. DNA-diagnosis is performed by blotting-analysis, a universal methodical approach. Recently a new highly effective method has been developed: a selective amplification of the DNA region under study by the polymerase chain reaction. It is possible to divide the DNA-diagnosis into four basic approaches. They are used: 1) when the damaged gene is known and its mutation is a polynucleotide anomaly in the structure; 2) when the damaged gene has a point mutation of the known nature: 3) when the damaged gene is known, but the nature of its mutations is unknown: 4) when neither damaged gene, not its mutation are known. DNA-diagnosis is now possible to apply in more than 100 hereditary diseases, including the most common diseases: cystic fibrosis, phenylketonuria, thalassemias, hemophilias, etc.